FORMAÇÃO DE UMA COMISSÃO DE TERAPIA INTRAVENOSA EM UM HOSPITAL PÚBLICO ESTADUAL - Silva, Cátia Pereira de Souza (2021)
Introduction: Intravenous therapy isan essential and complex therapeutic resource due to the risks of complications to which patients are exposed. It is noteworthy that management technologies organize the practice of intravenous therapy by systematizing this assistance, and promoting patient safety and qualification of professionals. It is an indispensable therapeutic resource for the hospitalized patient, frequently exercised by the nursing team, which demands issues related to the interface of professionals with technological innovations. Objectives: Organize a multi-professional intravenous therapy committee in a state hospital to implement good practices in IV therapy, develop the rules of procedure for this committee and develop protocols for interdisciplinary care in intravenous therapy. Method: This is an action research with a qualitative approach, carried out in a large state public hospital. The participants were 14 professionals from the multidisciplinary team from different sectors of the hospital. The data collection occurred in the period April 2020 to October 2020. The participants were divided into two groups. The first and last meeting took place with the two groups together, while the seven meetings for the development of the regiment and protocols, were held with separate groups. Results: The analysis of the transcripts of the dialogues, during the group meetings, defined the following categories: collective strategy for the organization of a therapy commission and development of the protocols. Products: The following products were developed: structuring of the internal regulations of the intravenous therapy and management technology committee consisting of two protocols; and two scientific articles Conclusion: Based on the structuring of an intravenous therapy commission, the internal regulations of the committee and two protocols based on scientific evidence with subsidies for quality care to adult patients undergoing intravenous therapy were developed. The management tools were elaborated with the effective participation of a multiprofessional team. The results of this study may help in the management of work processes and guarantee, especially to the nursing professional, safety in the care of patients undergoing intravenous therapy, through the standardization of preventive actions. This study reaffirms the need for scientific discussion about intravenous therapy and the involvement of a specific team in the development of standardized actions. Therefore, it is suggested that the process be carried out in a systematic and participatory way, that is, elaborated and implemented in a collective and multidisciplinary way.